Examining Witness Interest: The Obstacles of Testimony in Islamic Jurisprudence and Positive Law - Hijrian Angga Prihantoro (Justicia Islamica, 2024)
This study compares Islamic jurisprudence and positive law to explore the obstacles of testimony, focusing on the complexity and controversy surrounding witnesses' interests. Employing a legal comparative method, the research examines self-interest in testimony, emphasizing authoritative sources like fiqh books and Jordanian law, shedding light on the concept of self-interest as its primary focus. It highlights the differences between Islamic jurisprudence and contemporary legal frameworks, providing a nuanced understanding of witness actions in legal processes. This research's findings reveal that testimony's self-interest predominantly relates to lineage, siblinghood, marital relationships, hostility, and partisanship. The results show both Islamic jurisprudence and positive law recognize the prohibition of testimony due to self-interests is not absolute; there are many interpretations and exceptions to this restriction, with differences stemming from the reliance on religious texts in Islamic jurisprudence and legal reasoning in positive law. This gap arises from the ability of contemporary law to examine the interests of witnesses from various perspectives and through the use of different evidentiary tools. This research contributes practically that the application of law that is different from what has been formulated by fiqh scholars in Islamic jurisprudence does not necessarily indicate that the legal decision is at odds with Islamic law.